PENGARUH TREN PRODUK, STORE ATMOSPHERE, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN ULANG DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI - Annaufal, Muhamad Ardabilly; Prastowo, Sugeng Lubar; Syah, Hidayat (Jurnal Bisnis dan Manajemen (JBM), 2023)
This study uses customer satisfaction as the mediating variable to demonstrate how product trends, store ambiance, and word of mouth affect purchasing decisions. One hundred twenty-five participants took part in the study conducted at the Uniqlo Supermall Karawaci Tangerang. Tangerang and involved 125 respondents. The method used was quantitative, with the sampling technique using non-probability sampling with the accidental sampling method. Data analysis employed descriptive statistical techniques and inferential statistics using the structural equation modeling partial least squares (SEM-PLS) analysis tool with the SMART PLS 3.0 program. Keywords: Product trends, Store atmosphere, Word of Mouth, Satisfaction